Treatment of Severe Metabolic Alkalosis with Continuous Renal Replacement Therapy: Bicarbonate Kinetic Equations of Clinical Value. Issue 4 (July 2015) - Yessayan, Lenar; Yee, Jerry; Frinak, Stan; Kwon, David; Szamosfalvi, Balazs
Abstract : Concomitant severe metabolic alkalosis, hypernatremia, and kidney failure pose a therapeutic challenge. Hemodialysis to correct azotemia and abnormal electrolytes results in rapid correction of serum sodium, bicarbonate, and urea but presents a risk for dialysis disequilibrium and brain edema. We describe a patient with Zollinger–Ellison syndrome with persistent encephalopathy, severe metabolic alkalosis (highest bicarbonate 81 mEq/L), hypernatremia (sodium 157 mEq/L), and kidney failure despite 30 hours of intravenous crystalloids and proton pump inhibitor. We used continuous renal replacement therapy (RRT) with delivered hourly urea clearance of 3 L/hour (24 hour sustained low efficiency dialysis with regional citrate anticoagulation protocol at blood flow rate 60 ml/min and dialysate flow rate 400 ml/min). To mitigate a pronounced decrease in plasma osmolality while removing urea from this hypernatremic patient, dialysate sodium was set to start at 155 mEq/L then at 150 mEq/L after 6 hours. Serum bicarbonate, urea, and sodium were slowly corrected over 26 hours. This case demonstrates how to regulate and predict the systemic bicarbonate level using single pool kinetic modeling during convective or diffusive RRT. Kinetic modeling provides a valuable tool for systemic blood pH control in future combined use of extracorporeal CO2 removal and continuous RRT systems.